복합하중을 받는 원통형 적층복합재 구조의 파괴에 대한 열응력의 영향 - 조희근(Hee Keun Cho) (한국생산제조학회지, 2023)
As the mechanical behavior of cylindrical structures subjected to complex loads is very complex, predicting phenomena such as displacement, stress, and failure is very difficult. In this study, the effect of thermal stress due to temperature on the failure of a laminated composite cylindrical structure, in which tension, bending, and torsion are applied simultaneously, was evaluated through FEA numerical analysis. Five types of models: Tsai-Wu, Tsai-Hill, Puck, Hoffman, and Hashin, were used to predict the failure of a cylindrical laminated composite shell structure having eight layers. The type of composite failures appeared very different owing to the influence of thermal stress. Contrary to general predictions, we confirmed that thermal stress has a positive effect on failure in certain combinations of layer stacking angles in the case of cylinders. KCI Citation Count: 0